The Psycholinguistic Study of Language Acquisition and Communicative Processes - Arakelyan, Rouzanna (Armenian Folia Anglistika, 2011)
The article investigates the psycholinguistic characteristics of language acquisition and communicative processes. To this end, the natural process of speech articulation and the role of the creation of speech intention, situational factors of speech activity as well as different theories underlining the peculiarities of foreign language acquisition have undergone comprehensive examination in the first place. Neurolinguistic, linguistic and psycholinguistic approaches describing the process of language acquisition have been studied with utmost care and attention. The article highlights the necessity of entering the data of psycholinguistic investigations into the theoretical generalization of the questions discussed.